Conceptual Framework for Developing a Model of Effective Tree Preservation Order (Act 172) Implementation in Construction Projects - Nik Mohamed Sukri, Nik Adlin; Ismail, Zulhabri; Wan Ariffin, Wan Tarmeze (International Journal of Sustainable Construction Engineering and Technology, 2020)
Trees are important to human and the environment, and they must be preserved for the benefit of mankind. The Government of Malaysia has realized that the country’s rapid development is killing the trees especially due to construction activities. On that basis, the Tree Preservation Order (TPO) (Act 172) was introduced in 1996. However, from time to time, there were cases whereby the trees that were supposed to be preserved have been cut down for development without consent of the local authorities. This situation has raised questions about the effectiveness of implementing TPOs, especially pertaining to construction projects. Hence, this conceptual paper proposes a framework for the development of effective TPO implementation model in construction projects. It consists of four key components that must be taken into account to ensure better implementation. The formation of this conceptual framework was based on facts and knowledge obtained through literature review and document analysis.